Bilateral isokinetic peak torque of quadriceps and hamstring muscles in professional soccer players with dominance on one or both two sides - Zakas, A. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: Dominance of one leg may cause asymmetry between the contralateral muscle groups and develop predisposition for injury to the leg with the weaker muscle strength. The purpose of this study was to examine the strength balance in the extensor and flexor muscle groups, as well as the hamstring to quadriceps (H/Q) ratios of both legs in professional soccer players with dominance on one or both legs. Methods: Forty-two professional soccer players of the first Greek division participated in this study. Participants were divided into 3 groups according to their leg use during training sessions and matches. Fifteen players comprised the first group with dominance to the right leg, 12 players formed the second group with dominance to the left leg, and 15 players consisted the third group with dominance to both the right and left legs. Maximum voluntary concentric torque of the hamstring and quadriceps muscles of both legs was assessed using a Norm isokinetic dynamometer at angular velocities of 12°, 60°, 180° and 300°/s. Results: No significant differences in the strength balance found between the groups. The isokinetic variables comparing the right and left body side in each group, with dominance on one or both legs, did not differ. No differences were recorded in the H/Q between the right and left legs for any of the subject groups. Conclusion: There is no evidence of muscle imbalances in extensor and flexor muscle groups and H/Q ratios between the right and left legs in professional soccer players with dominance on one or both legs. The training sessions and matches appear to have imposed strength balance for the right and left body sides of professional soccer players.